Checkweigher using an emfc weighing cell with magnetic springs and air-bearings - Lee, Hyun Ho; Yoon, Kyung Taek; Choi, Young Man (Metrology and Measurement Systems, 2021)
A dynamic weighing system or a checkweigher is an automated inspection system that measures the weight of objects while transferring them between processes. In our previous study, we developed a new electromagnetic force compensation (EMFC) weighing cell using magnetic springs and air bearings. This weighing cell is free from flexure hinges which are vulnerable to shock and fatigue and also eliminates the resonance characteristics and implements a very low stiffness of only a few N/m due to the nature of the Halbach array magnetic spring. In this study, we implemented a checkweigher with the weighing cell including a loading and unloading conveyor to evaluate its dynamic weighing performances. The magnetic springs are optimized and re-designed to compensate for the weight of a weighing conveyor on the weighing cell. The checkweigher has a weighing repeatability of 23 mg (1σ) in static situation. Since there is no low-frequency resonance in our checkweigher that influences the dynamic weighing signal, we could measure the weight by using only a notch filter at high conveyor speeds. To determine the effective measurement time, a dynamic weighing process model is used. Finally, the proposed checkweigher meets Class XIII of OIML R51-1 of verification scale e 0.5 g at a conveyor speed of up to 2.7 m/s.
Keywords: Air bearing; Automated inspection systems; Cell-be; Cell/B.E; Cell/BE; Checkweighe; Dynamic weighing; Electromagnetic force compensations; Magnetic spring; Weighing systems; Checkweigher; Electromagnetic force compensation; Magnetic spring